Implementation of the "Al-Bahits Al-Qur'ani" Application to Increase the Effectiveness of Al-Qur'an Interpretation Studies - Husnia, Hilda; Azizah, Alfiyatul; Nugroho, Kharis (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
This study investigates the effectiveness of the "Al-Bahits Al-Qur'ani" application in enhancing the study of Qur'anic interpretation. Employing a mixed-method approach, the research combines quantitative data gathered through questionnaires with qualitative insights derived from literature review. The findings indicate that the use of the "Al-Bahits Al-Qur'ani" application significantly improves the efficiency and depth of Qur'anic interpretation studies. Its user-friendly features and search functionalities support better comprehension and access to tafsir resources. This study highlights the growing relevance of digital tools in Islamic scholarship and underscores the necessity for further innovation in the digitalization of Islamic sciences. The results contribute to the discourse on integrating technology in religious studies and provide a basis for future development of similar applications to support Islamic education.